Viability of rearing Telenomus sp. (Hymenoptera, Scelioniodae), an egg parasitoid of Helicoverpa armigera (Lepidoptera, Noctuidae), under laboratory conditions - Duarte, S.=700 1 Goncalves, C.I.; Figueiredo, E.; Quartau, J.A.; Mexia, A.; Amaro, F.
(En, Es)
Ilus., 26 ref.
Keywords: TELENOMUS; PARASITOS; RELACIONES HUESPED PARASITO; TOMATE; ESPAÑA; CRIA EN LABORATORIO